Anti-fibrotic Role of miR-214 in Thioacetamide-induced Liver Cirrhosis in Rats. (August 2015) - Izawa, Takeshi; Horiuchi, Takashi; Atarashi, Machi; Kuwamura, Mitsuru; Yamate, Jyoji
An increasing number of studies have focused on the role of microRNAs in liver fibrosis/cirrhosis. miR-214 has recently attracted more attention as a fibrosis-related factor; however, the molecular mechanisms in hepatic fibrogenesis remain largely unknown. Here, we investigate the pathological role of miR-214 during progression of liver cirrhosis in rats. Rats were injected intraperitoneally with thioacetamide at a dose of 100 mg/kg body weight, twice a week. The liver was collected at post first injection weeks 5, 10, 15, and 20. Hepatic expression of miR-214 was analyzed by real-time polymerase chain reaction, in situ hybridization, and laser microdissection. The effects of miR-214 overexpression were investigated by in vitro transfection using fibroblastic MT-9 cells. miR-214 was highly upregulated in the fibrotic area in parallel with the cirrhosis progression. miR-214 overexpression in MT-9 cells under transforming growth factor-β1 stimulation resulted in decreased cell number and increased expression of cleaved caspase 3 and decreased expression of α-smooth muscle actin, suggesting that miR-214 induces apoptosis and inhibits myofibroblast differentiation in fibroblastic cells under stimulation of fibrogenic factors. These data indicate an anti-fibrotic role of miR-214 in chemically induced liver fibrosis/cirrhosis.